Optimization of choice of basic and additional competitive distances reflecting individual qualified athletes- swimmers - Політько, О. В.; Пилипко, О. О. (Slobozhanskyi Herald of Science and Sport, 2011)
This article discusses issues related to the possibility of using methods of choosing the optimal combination of basic and additional competitive distances in contemporary swimming sport. Based on the analysis of performance of skilled swimmers of various specializations in the process of competitive activity, the authors experimentally defined the effectiveness of the developed technique.